The quality of motor cars and its variation in time - Mickūnaitis, Valentinas (Transport, 2004)
The paper considers the quality of motor cars and its changes during the vehicle service life. The process is analysed in terms of the theory of reliability. The emphasis is placed on the analysis of the work without breakdown and such issues as probabilities of breakdowns and breakdown‐free operation, breakdown frequency, intensity and the average time of the vehicle run till failure. Based on the statistical data breakdown probabilities of the particular systems, mechanisms and units, depending on the service life of a vehicle are determined.First Published Online: 27 Oct 2010